Design and Performance Analysis of a TLET-Type Flexure Hinge - Ngoc Le Chau; Ngoc Thoai Tran; Thanh-Phong Dao (Advances in Materials Science and Engineering)
In order to permit a large deflection, three lamina emergent torsional flexure hinges are reconfigured to create a new triple LET-type flexure hinge (TLET) in this paper. The TLET consists of flexure hinges in a series coupled with others in parallel configuration. This arrangement is aimed to enhance the displacement of the joint. The proposed joint is capable of generating a large displacement and a large capacity of load within safety working conditions. The closed-form models are derived to calculate the equivalent spring constant, rotation angle, and displacement of the proposed joint. Failure analysis of the TLET joint with different materials is conducted by finite element analysis. The closed-form models are validated by simulations and experimentations. The validated results are well coincided each other. The result found that the joint achieves a maximum large displacement of 16.97 mm in the x-axis with respect to a maximum load of 20 N. When the joint slides a maximum displacement of 16.97 mm along the x-axis, the output displacement emerges out the z-axis up to 23.12 mm, respectively. The joint can achieve an angle displacement of 38.92°. The displacement of the TLET joint is 2.4 times greater than that of the traditional LET joint. The proposed joint is considered for engineering applications where a large working stroke and a large capacity of load are expected.